RAGE interacts with the necroptotic protein RIPK3 and mediates transfusion‐induced danger signal release. Issue 8 (7th July 2020) - Faust, Hilary; Lam, LK Metthew; Hotz, Meghan J.; Qing, Danielle; Mangalmurti, Nilam S.
Abstract : RBC transfusion is associated with increased morbidity and mortality in critically ill patients. Endothelial cell necroptosis and subsequent damage‐associated molecular pattern (DAMP) release has been identified as a mechanism of injury following RBC transfusion. Mounting evidence implicates the pro‐inflammatory pattern recognition receptor, Receptor for Advanced Glycation End Products (RAGE), in initiating cell death programmes such as necroptosis. Here, we demonstrate the role of RAGE in endothelial necroptosis, as deletion of RAGE attenuates necroptotic cell death in response to TNFα, LPS or CpG‐DNA. We show direct interaction of RAGE with the critical mediator of necroptosis, Receptor Interacting Protein Kinase 3 (RIPK3), during necroptosis. Furthermore, we observe decreased plasma High Mobility Group Box 1 (HMGB1) and RIPK3 levels in RAGE deficient mice compared to WT mice post‐transfusion, substantiating the role for RAGE in transfusion‐induced DAMP release in vivo . Collectively, these findings underscore RAGE as an essential mediator of regulated necrosis and post‐transfusion DAMP release. Further studies to understand the role of RAGE and the necroptotic pathway in transfusion‐induced organ injury may offer key targets to mitigate transfusion‐related risks, including the risk of ARDS, in susceptible hosts.